1-(3-Pyridyl)pyrrolidine-2,5-dione - Hou, Hong-Bo (International Union of Crystallography, 2009)
In the title molecule, C(9)H(8)N(2)O(2), the dihedral angle between the pyridine and the pyrrolidine rings is 64.58 (12)°. In the crystal structure, weak C—H⋯π-electron ring interactions stabilize the packing.